Diagnostic Accuracy of TCD/AC Ratio in Predicting Intrauterine Growth Retardation - Naila Ashfaq, Umbreen Akram, Ruqya Zafar, Rabia Khalid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Fetal growth assessment is necessary for prediction of fetal health during pregnancy. Aim: To determine the diagnostic accuracy of transcerebellar diameter / abdominal circumference ratio in predicting intrauterine growth retardation after 20 weeks gestation taking birth weight as gold standard. Study design: Cross sectional study. Methodology: Present study was conducted at Department of Obstetrics & Gynecology, Combined Military Hospital Kharian. Patients (n=80) with an age range of 18-40 years with singleton pregnancies at 20 weeks gestation were enrolled. All patients were assessed by ultrasound and TCD/AC ratio was calculated. All patients followed till birth and actual birth weight was obtained. All this information was recorded on Performa. Statistical analysis: Data was analyzed using SPSS version 26. Results were presented as frequency and percentage. Age was presented as mean± SD. Results: The mean age of patients was 28.61±5.72 years. The mean gestational age was 21.96±1.50 weeks. For prediction of IUGR, TCD/AC had sensitivity, specificity, PPV, NPV & diagnostic accuracy of 85.29%, 91.3%, 87.88%, 89.36% & 88.75%, respectively. Conclusion: It was concluded that TCD/AC ratio is an accurate diagnostic tool accuracy for prediction of IUGR during pregnancy.